Intrathecal Morphine Following Lumbar Fusion: A Randomized, Placebo-Controlled Trial. Issue 2 (27th September 2018) - Dhaliwal, Perry; Yavin, Daniel; Whittaker, Tara; Hawboldt, Geoffrey S; Jewett, Gordon A E; Casha, Steven; du Plessis, Stephan
Abstract: BACKGROUND: Despite the potential for faster postoperative recovery and the ease of direct intraoperative injection, intrathecal morphine is rarely provided in lumbar spine surgery. OBJECTIVE: To evaluate the safety and efficacy of intrathecal morphine following lumbar fusion. METHODS: We randomly assigned 150 patients undergoing elective instrumented lumbar fusion to receive a single intrathecal injection of morphine (0.2 mg) or placebo (normal saline) immediately prior to wound closure. The primary outcome was pain on the visual-analogue scale during the first 24 h after surgery. Secondary outcomes included respiratory depression, treatment-related side effects, postoperative opioid requirements, and length of hospital stay. An intention-to-treat, repeated-measures analysis was used to estimate outcomes according to treatment in the primary analysis. RESULTS: The baseline characteristics of the 2 groups were similar. Intrathecal morphine reduced pain both at rest (32% area under the curves [AUCs] difference, P < .01) and with movement (22% AUCs difference, P < .02) during the initial 24 h after surgery. The risk of respiratory depression was not increased by intrathecal morphine (hazard ratio, 0.86; 95% confidence interval, 0.44 to 1.68; P = .66). Although postoperative opioid requirements were reduced with intrathecal morphine ( P < .03), lengths of hospital stay were similar ( P = .32). Other than a trend towards increased intermittent catheterization among patients assigned to intrathecal morphine ( P = .09), treatment-related side effects did not significantly differ. The early benefits of intrathecal morphine on postoperative pain were no longer apparent after 48 h. CONCLUSION: A single intrathecal injection of 0.2 mg of morphine safely reduces postoperative pain following lumbar fusion.